A transnational research agenda on the determinants, policies, and impacts of diaspora direct investments. (June 2022) - Naujoks, Daniel
Abstract: Diaspora actors can increase trade, investments, as well as exchange of technology and know-how between home and host countries. As almost half of the world's countries have adopted policy incentives to encourage diaspora direct investments, such flows have received considerable interest by scholars and governments alike. In a comprehensive scoping exercise, this essay highlights the critical contributions made by the existing literature on diaspora investment in the fields of international political economy, economics, business studies, transnational and migration studies, economic sociology, and ethnic entrepreneurship. Flagging existing shortcomings, the essay outlines an integrated, transdisciplinary, and transnational research agenda. If offers new lines of inquiry, methodological considerations, and suggestions for testable hypotheses that are needed to advance our understanding of the modalities, determinants, and impacts of diaspora investments, as well as the role of public policies. Offering new categorizations for diaspora investors and public policies, it suggests how analytical frameworks can make meaningful differentiations that account for the heterogeneity of diaspora populations, firms, investments, and contexts.